Civil War Aftermath and Reconstruction - Hamen, Susan E.; Elliott, Mark, 1969 September 23-; Essential Library (Firm) (Minneapolis, Minnesota : Essential Library, an imprint of Abdo Publishing, 2017)
Learn how the Civil War influenced different aspects of the Americans' lives including frontline soldiers, women at home, African Americans, and even the nation's leaders, while the Reconstruction era changed the society and daily lives of African American citizens.
The fall of Atlanta -- War -- Lincoln's Reconstruction -- Johnson's Reconstruction -- Reconstruction for African Americans -- Coming home -- Postwar progress and struggles -- Reconstruction ends -- The legacy of Reconstruction.
Includes bibliographical references (pages 104-109) and index.
Keywords: 1800-1899.; Reconstruction (U.S. history, 1865-1877) -- Juvenile literature; African Americans -- History -- 1863-1877 -- Juvenile literature; Reconstruction (U.S. history, 1865-1877); African Americans -- History -- 1863-1877.; African Americans; Influence (Literary, artistic, etc.); Race relations; United States -- History -- Civil War, 1861-1865 -- Influence -- Juvenile literature; United States -- Race relations -- History -- 19th century -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Influence; United States -- Race relations -- History -- 19th century; United States; History; Juvenile works